A Thermodynamic Equilibrium Of Nitrogen Plasma Species Reaction At Atmospheric Pressure: An Application for Afterglow - Saktioto Saktioto (Institut Teknologi Bandung, 2002)
Before producing nitrogen plasma at atmospheric pressure in experiment, a simulation is carried out to show the equilibrium processes by chemical kinetic reaction. Nitrogen species density is guided by continuity equation where chemical processes and Arrhenius form are used to follow the change of density over the time. Those formula are integrated to obtain density and the reaction rate of each reaction. This result show that the equilibrium can be reached and generally agree with the Saha Boltzmann calculation. An afterglow application is also shown in this model where the electron is dominant in collision and cooling time is in millisecond.